2018
DOI: 10.1021/acs.bioconjchem.7b00578
|View full text |Cite
|
Sign up to set email alerts
|

Vx3-Functionalized Alumina Nanoparticles Assisted Enrichment of Ubiquitinated Proteins from Cancer Cells for Enhanced Cancer Immunotherapy

Abstract: A simple and effective strategy was developed to enrich ubiquitinated proteins (UPs) from cancer cell lysate using the α-AlO nanoparticles covalently linked with ubiquitin binding protein (Vx3) (denoted as α-AlO-Vx3) via a chemical linker. The functionalized α-AlO-Vx3 showed long-term stability and high efficiency for the enrichment of UPs from cancer cell lysates. Flow cytometry analysis results indicated dendritic cells (DCs) could more effectively phagocytize the covalently linked α-AlO-Vx3-UPs than the phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…As mentioned previously, the success of peptide-based vaccines mainly depends on the utilized peptides and selection of an appropriate adjuvant. Herein, it has been found that the covalent linking of adjuvant to tumor-associated antigens (TAAs) could result in the maturation and activation of DCs in vitro and induced a potent antitumor immune response in vivo compared to TAAs which they physically mixed with adjuvant [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously, the success of peptide-based vaccines mainly depends on the utilized peptides and selection of an appropriate adjuvant. Herein, it has been found that the covalent linking of adjuvant to tumor-associated antigens (TAAs) could result in the maturation and activation of DCs in vitro and induced a potent antitumor immune response in vivo compared to TAAs which they physically mixed with adjuvant [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…These nanoparticles are ubiquitinated, allowing them to bind with selective autophagy receptor proteins, such as SQSTM1, and are then linked to an LC3-interacting region, resulting in autophagic machinery and degradation in lysosomes. [30][31][32] Several studies have reported the ubiquitination or Ub-decorated nanoparticles either directly [34,101,118,[178][179][180][181][182][183][184][185][186][187][188][189][190] or indirectly [191][192][193][194] for processing through the selective autophagy pathway ( Table 3). These nanoparticles may be delivered through the Ub-decorated mechanisms to mediate binding to autophagy receptors for entry into selective autophagy pathways.…”
Section: Interaction Of Ubiquitin and Nanoparticlesmentioning
confidence: 99%
“…Nanoparticles or nanodrugs may be decorated with Ub through different mechanisms. Previous studies have reported that nanoparticles were either directly [34,101,118,178,180] or indirectly [34,192,194] binding to Ub proteins. Thereafter, nanoparticles and nanodrugs attach to cargo to become engulfed by the phagophores through binding to ubiquitinated cargos, selective autophagy receptors, and LC3 regions, to form a double-membrane-vesicle nanoparticulosomes (Figure 5c,d).…”
Section: Three Possible Pathways Of Nanoparticulophagymentioning
confidence: 99%
“…Therefore, different strategies for UPs enrichment have been developed to achieve a clinically safe, simply made, and environment-friendly vaccine with enhanced antitumor immune response. [19][20][21] In our previous studies, we enriched UPs from tumor cells after proteasome inhibition by Ni-NTA agarose beads conjugated with ubiquitin-binding protein Vx3. We found that the UPs have the ability to be an effective cancer vaccine.…”
Section: Introductionmentioning
confidence: 99%